Booking off loan loans in regional companies regional owned business bank - Priambodo, Glemboh; Isnaeni, Moch; Prasetyawati, Endang; Setyadji, Sri (Technium Social Sciences Journal, 2022)
Financing analysts at Banks should be more thorough and careful in analyzing the data of prospective customers who want to apply for loans and not only using 5C analysis principle in conducting analysis but added using 5P analysis principle (Personality, Purpose, Prospect, Payment, Party) ,3R (Return, Repayment, Risk Bearing Activity), or with CAMEL principle (Capital, Asset Quality, Management, Earning, Liquidity) so as to minimize problematic financing and fraud committed by potential customers. To deal with debtors who have bad credit, it should be resolved properly, peacefully. This is to maintain the good name of each party, between bank and debtor. Write-off carried out by the Board of Directors must comply with criteria, requirements, limits, authorities, responsibilities and procedures that have been prepared by Board of Directors and approved by Board of Commissioners and with the bank's belief that the credit cannot be returned by debtor customer concerned from debtor's information, it can be seen that debtor's customer has experienced bad credit and improved collectibility due to write-off.